2021
DOI: 10.3390/molecules26133860
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Heme Oxygenase-1 Inhibition and Sigma Receptor Modulation for Anticancer Activity

Abstract: Cancer is a multifactorial disease that may be tackled by targeting different signaling pathways. Heme oxygenase-1 (HO-1) and sigma receptors (Rs) are both overexpressed in different human cancers, including prostate and brain, contributing to the cancer spreading. In the present study, we investigated whether HO-1 inhibitors and R ligands, as well a combination of the two, may influence DU145 human prostate and U87MG human glioblastoma cancer cells proliferation. In addition, we synthesized, characterized, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…Extending this effort, we recently identified SI 1/13, a selective benzylpiperazine-based S1R antagonist with a S2R/S1R selectivity ratio of 886 that demonstrated efficacy against chronic constrictive nerve injury (CCI)-induced neuropathic pain and formalin-induced inflammatory pain without impairing locomotor activity [ 22 ]. In addition, SI 1/13 demonstrated significant cytotoxic effects towards DU145 and U87MG cancer cells, further corroborating its function profile as a S1R antagonist [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 74%
“…Extending this effort, we recently identified SI 1/13, a selective benzylpiperazine-based S1R antagonist with a S2R/S1R selectivity ratio of 886 that demonstrated efficacy against chronic constrictive nerve injury (CCI)-induced neuropathic pain and formalin-induced inflammatory pain without impairing locomotor activity [ 22 ]. In addition, SI 1/13 demonstrated significant cytotoxic effects towards DU145 and U87MG cancer cells, further corroborating its function profile as a S1R antagonist [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 74%
“…Afterwards, the preparations were fixed in a humid incubator at 37°C after being placed in caps filled with vaseline. Then, the preparations were treated with ACSF (control) or apomorphine (10 μM, Himeno et al, 2011), metoclopramide (10 μM, Wolfes et al, 2021), haloperidol (10 μM, Romeo et al, 2021) and ondansetron (10 μM, Hur et al, 2014) or their combinations, respectively; 250 μL of incubation medium was collected for each treatment at 10 min intervals and was mixed with 20 μL of aprotinin to prevent the degradation of CGRP. The aliquots were stored at −20°C until CGRP measurement.…”
Section: Methodsmentioning
confidence: 99%
“…In a study conducted by Romeo et al, it was observed that sigma receptors, non-G protein-coupled receptor (GPCR) transmembrane proteins, are expressed in various cancer cell lines. Their two subtypes, σ-1R and σ-2R, are, respectively, antagonized and agonized to promote cancer inhibitory effects [80]. When exposing DU145 cells to sigma receptor ligands, it was found that cell proliferation was noticeably reduced by approximately 50%.…”
Section: Inhibition Of Ho-1 By Xenobiotics In Pca Modelsmentioning
confidence: 99%
“…When exposing DU145 cells to sigma receptor ligands, it was found that cell proliferation was noticeably reduced by approximately 50%. When used in combination with HO-1 receptors, it was found that exposure to 10 µM of both the ligand and inhibitor greatly reduced proliferation by 75% [80]. This response suggests that while targeting the use of either an inhibitor or sigma receptor is effective in the reduction in cell viability, the greatest effect comes from multi-targeted combination therapy.…”
Section: Inhibition Of Ho-1 By Xenobiotics In Pca Modelsmentioning
confidence: 99%
See 1 more Smart Citation